A Critical Analysis of Death Penalty in Nigeria - Olatunbosun, Ismaila Adeniyi (2015)
This study analysed the practice of the death penalty in Nigeria, examined the underlying principle of retributive punishment for the offenders and assessed the administration of death sentence through the mode and manner of execution with a view evaluating the perception of the public and appraising the constitutionality of the death penalty in Nigeria.